'Digital pills' for mental diseases: an ethical and social analysis of the issues behind the concept. Issue 1 (27th July 2020) - de Miguel Beriain, Iñigo; Morla González, Marina
Abstract: Recently, the US Food and Drug Administration has given a landmark approval to the very first digital pill with a sensor embedded in the inside. These are complex systems that include a drug and an electronic tracker that is activated when the patient takes the pill. Accordingly, they might be an excellent tool for monitoring and potentially improving patients' adherence to prescriptions. This would serve well to avoid unnecessary healthcare costs and reduce the anxiety of patients and their relatives. However, digital pills might also diminish patient autonomy, reduce privacy, or promote inadequate use of pharmaceutical resources. This article is aimed at contributing to adequate use of this new tool by showing the main ethical and social issues they involve and proposing measures meant to address them. Finally, we conclude by defending the idea that these new systems should be seen as means of complementing traditional strategies to promote adherence to treatment, and not as substitutes.